Agama, Masyarakat dan Media Masa - Nesia Mu’asyara; Ashariyansah Ashariyansah; Elvan Triadi; Risma Wati; Intan Nuraini; Rahmanda Satiroh; M. Agung Pratama; Afrizal Luthfi Abdillah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
In the Digital Age, digital media—especially the internet and social media—has profoundly changed the way people communicate and interact with each other. The development of this technology has provided several benefits, including the creation of virtual communities, easy access to information, and the ability to engage in discussions. In addition, digital technology influences the way people worship and improves interpersonal relationships and communication. Although digital technology offers many advantages in terms of social interaction and access to information, it is important to monitor and ensure that digital technology is used responsibly and in a way that benefits society as a whole. This study uses a descriptive, qualitative research approach with triangulation data collection, the object of this study is social media accounts used by the community. A qualitative descriptive approach is used to analyze and interpret the content of religious media. The author can analyze the text, images, or videos in religious media to understand the messages conveyed, the representation of religion, or the communication patterns that occur. Based on the results of the study, there are advantages and disadvantages in the relationship between human life and technological advances, especially mass media. Although religious messages and public understanding are greatly enhanced by mass media, there are also disadvantages, such as the spread of misleading information. To reduce the negative impact of mass media, it is important to use it responsibly and monitor it.